Professional and personal traits of the teacher and the relationship with didactic strategies - Chamorro-Atalaya, Omar; Gonzáles-Pacheco, Anthony; Quipuscoa-Silvestre, Manuel; Durán-Herrera, Víctor; Suarez-Bazalar, Raul; Vargas-Díaz, Ademar; Villanueva-Acosta, Víctor; Moreno-Chinchay, Lilly (Institute of Advanced Engineering and Science, 2024)
During the context of virtual classes due to the pandemic, it was evidenced that many teachers had to face accelerated adaptation stages, which is why teachers presented difficulties in designing their teaching strategies and students showed certain difficulties in their learning. In this sense, this article aims to determine how the professional and personal traits of the teacher are related to their teaching strategies, in the context of COVID-19, from the perspective of the students. For which an investigation was developed with a quantitative approach, correlational level and non-experimental design. It was determined that there is a moderate direct relationship between the professional and personal traits of the teacher with his didactic strategies in the context of virtual teaching. Thus, it was also identified that teachers do not pour their professional experiences into the development of the subject, additionally it does not favor the solution of problems related to real life applications; this leads teacher to reflect on the importance of the construction of student knowledge, especially if it is about subjects that are taught in the last cycles, since the student is waiting for how and in which processes their knowledge will be applied theoretical knowledge.